The Existency of Sangkar Burung Handicraft in Ciloa Village as Social Studies Learning Sources: Eksistensi Kerajinan Sangkar Burung di Desa Ciloa Sebagai Sumber Pembelajaran IPS - Mulyani, Siti; Widyanti, Triani; Mulyana, Eldi (SAHUR Journal, 2022)
The use of learning resources at this time does not only depend on books, especially for social studies lessons which of course the study of the material is closely related to social issues. Global economic competition is certainly a challenge for social studies educators to be able to equip their students to have the ability to collaborate so as to create a competent golden generation, one of the movements in the field of education is by making meaningful learning through the use of contextual learning resources. The purpose of this study is for students to have social skills and to develop scientific treasures related to components in the bird cage handicraft business by making it a social studies learning resource. This study uses a qualitative approach with a qualitative descriptive method using observation, interviews and documentation. The results of the study can be summarized into three main points: 1) The transition of the bird cage handicraft business. The community of Ciloa, Mekarsari Village, Selaawi District, which is increasing, provides an overview of economic activities and entrepreneurship so that it can be used as a source of social studies learning at SMP Negeri 1 Selaawi. 2) The existence of bird cage craftsmen provides many benefits to various groups, especially in the social and economic fields so that the existence of bird cage crafts needs to be maintained. 3) The support of social studies educators for implementing bird cage crafts at SMP Negeri 1 Selaawi gives strength to students to learn how the components of bird cage handicraft business are in the hope that students have the ability to maintain bird cages as one of their regional characters so that students have economic provisions in entrepreneurship.